Safe use of pesticides : ninth report of the WHO Expert Committee on Vector Biology and Control, meeting held in Geneva from 11 to 17 September 1984 - WHO Expert Committee on Vector Biology and Control; World Health Organization (Geneva : World Health Organization, 1985)
Presents fundamental changes in the approach to vector control recommended by WHO. These changes reflect both advances in knowledge and altered patterns of vector-borne disease that have occurred since the last report appeared in 1979. The report incorporates new knowledge on the toxicology of pesticides, issues raised by the development of new mutants and by genetic engineering, increased knowledge of the effects of human exposure to specific compounds, and new strategies for the protection of humans and the prevention and treatment of poisoning. In establishing advice for the safe use of pesticides, the report gives special attention to the need for risk-benefit analysis. The report also covers recommendations for protection of people using pesticides as well as for the safe disposal of used containers.
1. Introduction -- 2. Review of new data on insecticides for control of vectors -- 3. Review of selected compounds for control of rodents and molluscs of public health importance -- 4. protection of people who use pesticides -- 5. Prevention and treatment of poisoning -- 6. Summary of recommendations -- Acknowledgements -- References -- Annexes.
Keywords: Pesticides; Communicable Diseases and their Control